Peculiarities of test design and assessment of students’ outcomes in a foreign language - Zhukova, Tetiana; Жукова, Тетяна Василівна; Жукова, Татьяна Васильевна (My University, 2020)
EN: The importance and the main objectives of assessment in the learning process are substantiated in the article. Assessment is used to check if learning has taken place, for example: the skills, competence, knowledge, understanding needed at any given point. If we didn’t assess, we wouldn’t know whether learning had taken place, the teaching may have, but no learning achieved. Assessment should focus on improving and reinforcing learning as well as measuring achievements. It helps learners identify their progression and what they need to do to improve and progress further. Assessment is a regular process; it might not always be formalized, but we will be observing what our learners are doing, asking them questions, and reviewing their progress whenever we are in contact with them. The learners will be demonstrating their knowledge and skills regularly, for example through activities, discussions and regular tasks. The basic phases of test development are described: the design phase when the test features are developed and sample materials are written; the operational phase which involves the construction of a complete test; the monitoring phase when materials are revised and updated. Different tasks that are used in test design, their relevance and meaningfulness are lighted in the article. The most important things in test or task design have been analyzed. The task must be appropriate for the skill being assessed. The test is to be fair to the test taker. And the test should be accurately scored. The main types of tasks used to test listening skills (picking out a word, recognizing the correct tense, deducing meaning of unknown words from context, identifying the main ideas, listening for specific information) are presented. The main assessment criteria for speaking, reading, listening and writing are presented in the paper. As the process of assessment is a complicated one we must be certain that our tests are appropriate, fair and accurately scored. Modern teaching must ensure that testing has a positive impact on the learning process and motivation of students. We are therefore constantly making judgments about learners’ progress and how they could improve. We should also be aware of the impact that our feedback comments and decisions can have on their confidence. Comments which specifically focus on the activity or work produced will be helpful to our learners. UK: У статті обґрунтовано важливість оцінювання та його основні цілі у процесі навчання. Оцінювання використовується для перевірки того, чи відбулося навчання, наприклад, із метою перевірки набутих навичок, компетентності, рівня знань, розуміння. Якби ми не оцінювали, ми б не знали, чи було навчання, яких успіхів було досягнуто, які труднощі треба подолати. Оцінювання має бути зосереджено на вдосконаленні навчання, а також вимірюванні досягнень. Це допомагає учням визначити свій прогрес і те, що їм потрібно зробити для вдосконалення та подальшого прогресу. Оцінювання є регулярним процесом; воно не може бути формальним, і ми повинні спостерігати за тим, що роблять наші учні, ставлячи їм питання та переглядаючи їх прогрес, коли ми контактуємо з ними. Проаналізовано найважливіші речі в розробці завдань тестів. Завдання має відповідати вмінню, що оцінюється. Тест має бути справедливим до учасника тесту і правильно оцінений. Описані основні фази розробки тесту: фаза проектування, коли розробляються характеристики тесту та пишуться зразкові матеріали; операційний етап, який передбачає побудову всього тесту; етап моніторингу, коли матеріали переглядаються й оновлюються. У статті висвітлюються різні типи завдань, що використовуються при складанні тестів, їх актуальність та осмисленість. Представлені основні типи завдань, які використовуються для перевірки навичок аудіювання (добір слова, розпізнавання правильного часу, визначення невідомих слів із контексту, визначення основних ідей, прослуховування конкретної інформації). У статті представлені основні критерії оцінювання мовлення, читання, слухання та письма. Отже, ми постійно робимо висновки про прогрес студентів і про те, як їх знання могли б покращитися. Оскільки процес оцінювання є складним, ми повинні бути впевнені, що наші тести є відповідними, справедливими та точно оціненими. Один із найкращих способів допомогти студентам зрозуміти, що буде оцінюватися, – це обговорити з ними критерії оцінювання. Робота зі студентами над розробкою рубрик та інших інструментів оцінювання – це потужний спосіб допомогти їм зрозуміти, як виглядають відповідні тести та вимоги до них. Сучасне вчительство має дбати, щоб тестування мало позитивний вплив на процес навчання та мотивацію студентства.
Особливості складання тестів та оцінювання досягнень студентів при вивченні іноземної мови
Keywords: assessment; test development; validity; reliability; assessment criteria; motivation; achievements; оцінювання; розробка тестів; вагомість; надійність; критерії оцінювання; мотиваці; навчальні досягнення